Penguatan Kesejahteraan Psikososial Anak Melalui Praktikum Pelayanan Sosial di Panti Asuhan Muhammadiyah Abepura, Jayapura - Lobo, Albertina Nasri; Patanduk, Eddy; Taufik, Muhammad; Waroy, Novita; Bleskadit, Debora; Amiyaram, Yuliana (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
Children’s psychosocial well being often has abroad impact on their social relationship within the surrounding environment. Childrens living in orphanages have various needs and limitations that require the commitment of multiple stakholders, including in the area of inclusive social services. This study aims to identify and enhance the dynamics of social services orphanages to ensure their relevance and benefit. Observation, interviews and learning assistance metods were employed to understand the children’s social interaction skills and emotional development. The results of the community service indicate that the children gained knowledge and techniques to manage their psychosocialconditions independently and measurably. They also learned how to detect early signs related to their social-well-being. Continuous involvement rom orphanage management, supervisors, and partner institusions provides opportunities for social workers ti strengthen psychosocial services and community-based skill, allowing children to develop enthusiasm for improving their psychosocial well being during their stay in the orphanage.